2020
DOI: 10.1021/acs.macromol.0c00972
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Experimental and Molecular Simulation Study of the Entropic Viscoelasticity of End-Linked Polymer Networks

Abstract: Bifunctional vinyl-terminated poly(dimethylsiloxane) chains are endlinked by tetrafunctional tetrakis(dimethylsiloxy)silane cross-linkers to produce irregular polymer networks with controlled stoichiometric imbalance and extent of reaction. The results are used as input to create comparative, nominally the same, three-dimensional Monte Carlo computer microstructures. Stress relaxation laboratory measurements and bead-spring molecular dynamics (MD) simulations are performed to estimate the relaxation shear modu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 48 publications
1
25
0
Order By: Relevance
“…In simulations, structural defects and slow relaxation often necessitate large time and length scales, something that is extremely challenging in molecular dynamics simulations . Coarse-grained and mesoscopic simulation techniques are capable of accessing these scales but usually have the disadvantage of employing soft-core potentials .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In simulations, structural defects and slow relaxation often necessitate large time and length scales, something that is extremely challenging in molecular dynamics simulations . Coarse-grained and mesoscopic simulation techniques are capable of accessing these scales but usually have the disadvantage of employing soft-core potentials .…”
Section: Introductionmentioning
confidence: 99%
“…In simulations, structural defects and slow relaxation often necessitate large time and length scales, something that is extremely challenging in molecular dynamics simulations. 27 Coarse-grained and mesoscopic simulation techniques are capable of accessing these scales but usually have the disadvantage of employing soft-core potentials. 28 As a result, polymer chains and network strands may cross each other, which prevents these methods from correctly sampling related physical phenomena such as reptation 29 and in-tube relaxation.…”
Section: ■ Introductionmentioning
confidence: 99%
“…The Miller–Macosko model for nonlinear polymerization with w sol data enables us to evaluate the structural parameters of infinite networks, as was often done in previous studies. ,, The model relates the extent of reaction ( p ) for a functional group in the cross-linker with w sol . A recent study showed that the p values estimated using this approach agreed with those obtained directly in Monte Carlo simulations for the end-linked tetrafunctional PDMS gels prepared at 0.7 < r < 1.3. We apply this approach to the gels with various values of r ranging from the stoichiometric ratio ( r = 1) to the near-critical compositions, although the strict validation of the applicability to the vicinity of gel point remains to be accomplished.…”
Section: Results and Discussionmentioning
confidence: 61%
“…Elastomers (cross-linked polymer networks) have gained much attention over the years owing to their vast variety of applications from drug delivery devices to vibration damping and noise cutting applications to automobile tires. , End-linked networks, elastomers in which polymer chains are connected to the network only by their ends, are highly examined by researchers due to their simplicity as well as their well-defined properties, which render them suitable candidates to be described theoretically and replicated computationally. Arguably, one of the most well-studied end-linked networks is polydimethylsiloxane (PDMS).…”
Section: Introductionmentioning
confidence: 99%
“…Although polymer networks commonly also include trapped entanglements, it is outside of the focus of this work. Loops, on the other hand, which comprise another important network imperfection, are more probable to form in gels rather than in polymer networks prepared in the molten state. , Dangling structures arise naturally during the end-linking process especially when more active precursors’ ends are present, r <1 . Further to this, as the end-linking process proceeds, it slows down at the end of curing, most likely due to the low concentration of the reactants and steric hindrance as well as topological restrictions that constrain the polymer motions .…”
Section: Introductionmentioning
confidence: 99%